A contribution to the investigation of time-sharing ability - Šverko, Branimir (Array, 1983)
The aim was to investigate whether a distinct time-sharing factor is involved in performance of complex tasks. Three complex tasks were used, each of which consisted of two simple component tasks. On each of five consecutive days 51 subjects performed all these tasks, both complex and simple, twice: once singly and once concurrently with an additional loading task. The performances of the nine tasks (i.e. three complex and six simple) recorded under both conditions were intercorrelated and factor analysed. Four factors emerged, among which one was interpreted as a time-sharing factor.